A dual-mode sensing platform for the detection of glucose based on the Au NPs@Fe-MOF with dual enzyme activity - Wenrong Cai; Luyao Yin; Datong Wu; Junyao Li; Laidi Xu; Yong Kong (Food Chemistry, 2026)

Development and characterization of a novel compensating wheat–Dasypyrum villosum interstitial translocation line Dv6-IT1 carrying the powdery mildew resistance gene PmV - Renhui Zhao; Wentao Wan; Man Xu; Tiantian Chen; Ling Wang; Ronglin Wu; Shujiang Zang; Zunjie Wang; Wei Jiang; Datong Liu; Yong Zhang; Xiue Wang; et al. (Theoretical and Applied Genetics, 2026)

Telomere-to-telomere genome assembly reveals the genomic architecture of disease resistance and yield coordination in elite wheat YM33 - Guofeng Lv; Yating Wang; Heping Zhang; Yuning Shen; Wenjing Hu; Datong Liu; Mengmeng Liu; Wenna Wang; Yuwen Gao; Caixia Lan; Tongde Bie; Hongya Wu; et al. (Molecular Plant, 2026)

A colorimetric and electrochemical dual-mode sensor based on the morphological evolution of Au@Ag nanostars for quantitative silver ion detection - Junyao Li; Yujie Wang; Ling Cai; Zheyuan Lin; Zhengxiao Jiang; Peiming Liu; Wenrong Cai; Datong Wu; Zheng-Zhi Yin; Yong Kong (Journal of Environmental Chemical Engineering, 2025)

Impact of Open Crop Straw Biomass Burning Emissions on the Air Pollution in the Hunan Province, China: A Case Study - Datong Luo; Lin Luo; Na Wang; Jianxun Wu; Lang Liu (Aerosol Science and Engineering, 2025)
Emissions from open crop straw burning (OCSB) during crop harvest have exerted considerable impacts on the air quality in China, but the quantitative evaluation of OCSB to air pollutants remains insufficient. In the study, the WRF-Chem model is used to quantitatively evaluate the impacts of OCSB on the air quality in Hunan, China from October 15 to 26, 2024. During the study episode, OCSB contributes 45.7% and 16.8% of the anthropogenic emission of organic carbon and non-methane volatile organic compounds, respectively. Model simulations show that OCSB emissions account for 2.8% of the maximum daily 8-hour average ozone (MDA8 O 3 ) concentration, but play a more substantial role in particulate pollution, contributing 25.6% to near-surface fine particulate matter levels. OCSB is an important organic aerosol (OA) source, increasing primary OA by 46.2% and secondary OA by 62.7%. The enhanced OA accounts for 54.8% of the total PM 2.5 increase induced by OCSB emissions. Sensitivity experiments show that the concentrations of aerosol species generally decrease linearly with reduced OCSB emissions, while MDA8 O 3 concentrations exhibit a non-linear trend due to the complex responses to its precursors. Implementing the clean disposal of straw residue during crop harvest presents an effective strategy to improve the air quality in Hunan.

Melamine foam supported NiCo2S4/Ag nanowires with charging/discharging induced activation effect for asymmetric supercapacitors - Xingyue Wu; Yiping Qiu; Wenrong Cai; Junyao Li; Datong Wu; Laidi Xu; Yong Kong (Chemical Engineering Journal, 2024)

Association of CDKN1B gene polymorphisms with susceptibility to breast cancer: a meta-analysis - Heping Xiang; He Li; Weiwei Ge; Weidong Wu; Ming Gao; Wei Wang; Lei Hong; Datong Jiang; Changle Zhang (Molecular Biology Reports, 2013)